A REVIEW OF ISLAMIC CRIMINAL LAW ON THUGHTHROUGH ON THE NORTH SUMATRA-RIAU BORDER - Muhammad Fauzan Husin; Ramadani Ramadani (Program Pascasarjana UIN Sumatera Utara, 2025)
Thuggery is a social phenomenon that often causes unrest and threatens public security, particularly in the North Sumatra-Riau border region. Thuggery in this region is often associated with violence, extortion, robbery, and threats carried out by groups or individuals. This study aims to examine thuggery from the perspective of Islamic criminal law, highlighting the causal factors, forms of action, and sanctions that can be imposed on perpetrators. The research uses a normative juridical method with a statutory and sociological approach. The results indicate that the main factors driving thuggery are difficult economic conditions, low levels of education, and weak law enforcement. In Islamic criminal law, acts of thuggery that contain elements of violence and threats to public security can be categorized as jarimah hirabah, namely crimes that damage public security and are considered major sins. Sanctions for perpetrators of hirabah are very severe, such as the death penalty, crucifixion, amputation, or exile, according to the severity of the crime committed, as stated in the Qur'an Surah Al-Maidah verse 33. This finding confirms that Islamic criminal law views thuggery as a serious crime that must be dealt with firmly to create security and public order. Effective law enforcement as well as a preventive and educational approach are essential to reduce the number of thuggery in the North Sumatra-Riau border region.